Fast identification of reliable hosts for targeted cell line development from a limited‐genome screening using combined φC31 integrase and CRE‐Lox technologies. (3rd September 2013) - Crawford, Yongping; Zhou, Michelle; Hu, Zhilan; Joly, John; Snedecor, Brad; Shen, Amy; Gao, Albert
Abstract : The use of targeted integration (TI) in cell line development (CLD) usually introduces one copy of a recombinant gene into a predetermined transcriptionally active locus. This reduces the heterogeneity typically associated with traditional random integration (RI) CLD with regards to varied productivity and instability, resulting from diverse chromosomal influences, varied copy numbers, and repeat‐induced rearrangement. As such, TI CLD offers the hope of a predictable and consistent CLD process for establishing stable clones. However, given the low copy number, cell lines established from a TI CLD process tend to exhibit low productivity. Here, we describe our nonviral‐based approach for quickly establishing and identifying TI hosts from a limited genome screening. Importantly, the TI hosts identified are consistent and reliable in supporting the production of diverse antibodies regardless of antibody subclass (IgG1 vs. IgG4) or prior traditional CLD performance (relatively easy vs. difficult to express antibodies). Moreover, an approximately twofold increase in titer can be achieved by using a CRE recombinase‐mediated cassette exchange (RMCE) strategy with an exchange vector carrying two units of the antibody gene. Two RMCE hosts that were established were able to produce up to ∼1.7 and 2 g/L of antibodies in nonoptimized fed‐batch shake flask production cultures with chemically defined media. Potentially, this strategy may be applied to the production of bispecific antibodies with a fast turnaround time. © 2013 American Institute of Chemical Engineers Biotechnol. Prog ., 29:1307–1315, 2013